The limits of social science : causal explanation and value relevance - Hammersley, Martyn (SAGE, 2016)
This work engages with key intellectual challenges facing social science today, at a time when it is under considerable pressure to demonstrate its value. It addresses questions that carry implications for research practice, quantitative or qualitative, by making use of contemporary examples, such as the London riots.